Prayer and the transformation of the self in early Christian mystagogy - Loon, Hans van, 1951-; Nie, Giselle de; Op de Coul, Michiel; Egmond, Peter van (Late antique history and religion, 2018)
"This book is the second in a series on the mystagogy of the Church Fathers produced by the Netherlands Centre for Patristic Research. The first volume, Seeing through the Eyes of Faith: New Approaches to the Mystagogy of the Church Fathers (LAHR, 11), initiated the study of the Church Fathers as mystagogues, since this approach does more justice to the Fathers' own intention in writing a work or a sermon than does regarding them as theologians avant la lettre. Early Christian writers did not primarily seek to offer rational reflection on the faith as an objective in its own right, but their works were rather aimed at an existential transformation in their audience. The present volume focuses on how the Church Fathers conceived prayer as an aspect of such a process of progressive transformation, and as a means to achieve an awareness of God as Mystery, with whom one could, paradoxically, communicate in prayer. In the essays collected here many aspects and dimensions of the mystagogy of early Christian prayer are examined: different kinds of prayer, their antecedents and their development over time; their historical, theoretical, and ritual contexts and meanings; and their noetic, imaginative, and physical strategies."--